Dietary vitamin E affects small intestinal histomorphology, digestive enzyme activity, and the expression of nutrient transporters by inhibiting proliferation of intestinal epithelial cells within jejunum in weaned piglets - Chen, Cancan; Wang, Zhaobin; Li, Jianzhong; Li, Yali; Huang, Pengfei; Ding, Xueqin; Yin, Jia; He, Shanping; Yang, Huansheng; Yin, Yulong (Journal of animal science, 2019)
Vitamin E ( VE ) is an indispensable vitamin in piglet feed formula. Among other things, it affects tissues including small intestine tissues and in particular its major unit intestinal epithelial cells. Previously, limited in vivo experiments have focused on the effect of VE on the intestine, particularly digestion and absorption. VE has been shown to inhibit proliferation of some types of cells. This experiment was conducted to test the hypothesis that VE affects intestinal functions by influencing the intestinal epithelial cell proliferation. Thirty 21-d old weaned [(Yorkshire × Landrace) × Duroc] piglets with BWs of 6.36 ± 0.55 kg were randomly divided into five VE-containing feeding formula groups. The treatments were (i) 0 IU (control), (ii) 16 IU, (iii) 32 IU, (iv) 4. 80 IU, and (v) 5. 160 IU. The treatments lasted 14 d. At the end of the experiment, all subjects were sacrificed to obtain blood and tissue samples. The results suggest that VE did not affect the growth performance. VE did tend to decrease jejunal crypt depth (linear, P = 0.056) and villus width (linear, P < 0.05). Sucrase activity significantly decreased in the adding 80 IU VE compared with the control ( P < 0.05). Jejunal crypt, cell proliferation in 80 IU group significantly decreased compared with the control group ( P < 0.05). This study suggests that dietary VE may affect intestinal morphology and functions by inhibiting weaned piglet jejunal epithelial cell proliferation.